Relationship between the gut microbiota and bile acid composition in the ileal mucosa of Crohn’s disease - Bamba, Shigeki; Inatomi, Osamu; Nishida, Atsushi; Ohno, Masashi; Imai, Takayuki; Takahashi, Kenichiro; Naito, Yuji; Iwamoto, Junichi; Honda, Akira; Inohara, Naohiro; Andoh, Akira (Intestinal research, 2022)
Background/Aims: Crosstalk between the gut microbiota and bile acid plays an important role in the pathogenesis of gastrointestinal disorders. We investigated the relationship between microbial structure and bile acid metabolism in the ileal mucosa of Crohn’s disease (CD).Methods: Twelve non-CD controls and 38 CD patients in clinical remission were enrolled. Samples were collected from the distal ileum under balloon-assisted enteroscopy. Bile acid composition was analyzed by liquid chromatography-mass spectrometry. The gut microbiota was analyzed by 16S rRNA gene sequencing.Results: The Shannon evenness index was significantly lower in endoscopically active lesions than in non-CD controls. β-Diversity, evaluated by the UniFrac metric, revealed a significant difference between the active lesions and non-CD controls (P=0.039). The relative abundance of Escherichia was significantly higher and that of Faecalibacterium and Roseburia was significantly lower in CD samples than in non-CD controls. The increased abundance of Escherichia was more prominent in active lesions than in inactive lesions. The proportion of conjugated bile acids was significantly higher in CD patients than in non-CD controls, but there was no difference in the proportion of primary or secondary bile acids. The genera Escherichia and Lactobacillus were positively correlated with the proportion of conjugated bile acids. On the other hand, Roseburia, Intestinibacter, and Faecalibacterium were negatively correlated with the proportion of conjugated bile acids.Conclusions: Mucosa-associated dysbiosis and the alteration of bile acid composition were identified in the ileum of CD patients. These may play a role in the pathophysiology of ileal lesions in CD patients.